2015
DOI: 10.1002/pc.23385
|View full text |Cite
|
Sign up to set email alerts
|

Expanded graphite (EG) as a potential filler in the reduction of percolation threshold of multiwall carbon nanotubes (MWCNT) in the PMMA/HDPE/EG/MWCNT nanocomposites

Abstract: A facile route for the development of a conducting hybrid polymer nanocomposites composed of poly(methyl methacrylate) (PMMA)/high density polyethylene (HDPE) filled with multiwall carbon nanotube (MWCNT) and expanded graphite (EG) has been described. The EG used in this study was prepared by simple chemical exfoliation of graphite flakes and characterized by spectroscopic as well as morphological analysis. An industrially feasible melt mixing process was used for the preparation of the nanocomposites through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…The expanded graphite was accordion-like or worm-like and had a large number of network-like pores in its structure. Expanded graphite consisted of stacked layers of sp 2 hybridized carbon atoms bonded covalently in a hexagonal arrangement within the layer, and these layers were bonded to each other by weak van der Waals forces [27,28]. Many functional groups like carbonyl exist on the surface of EG.…”
Section: Introductionmentioning
confidence: 99%
“…The expanded graphite was accordion-like or worm-like and had a large number of network-like pores in its structure. Expanded graphite consisted of stacked layers of sp 2 hybridized carbon atoms bonded covalently in a hexagonal arrangement within the layer, and these layers were bonded to each other by weak van der Waals forces [27,28]. Many functional groups like carbonyl exist on the surface of EG.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, carbon nano‐tube and graphene are considered as primary fillers for preparing polymer based composites with high thermal conductivity because their excellent intrinsic thermal conductivity (above 1000 W/m K) and large aspect ratio (above 100) . Actually, researchers have tried different methods to compose EG with polymer matrix, including mechanical mixing and in situ exfoliation technology, in order to obtain polymer composites with elevated thermal conductivity . The results in this research indicate that EG is also candidate filler for improving thermal conductivity of TIMs.…”
Section: Resultsmentioning
confidence: 96%
“…Figure 2 shows the XRD patterns of PVDF/EG, PVDF/GO, and PVDF/rGO composites. It can be seen that PVDF/EG composites exhibit a strong peak at 2 ¼ 26.6 associated with the diffraction of (002) planes of EG, 22 and the peaks located at 17.7 , 18.4 , and 19.9 are characteristic peaks of -phase crystals of PVDF. The addition of GO into PVDF leads to the presence of peak at 2 ¼ 10.8 , corresponding to the basal plane (001) of GO, and the diffraction peak in the vicinity of 20.2 is ascribed to the and -phase crystals of PVDF.…”
Section: Resultsmentioning
confidence: 99%
“…EG is another kind of two-dimensional graphite nanoplate and comes from the expansion and exfoliation of the graphite intercalation compounds, resulting in its lower mass density and porous vermicular structure. 21,22 Additionally, the relative low cost and easy production of EG make its composites cost-efficient as compared to other carbon nanofiller composites. He et al 23 found that the dielectric permittivity of PVDF/EG composites improved dramatically near the percolation threshold, and also an abrupt increase in the dielectric loss.…”
Section: Introductionmentioning
confidence: 99%